Antimicrobial Glycopeptides: Synthesis and Antibacterial Activity of N-linked and O-linked Smaller Chain Glycopeptides - Nagarajan, K.; Taleuzzamman, M.; Kumar, V.; Singh, S.; Singh, J.; Panda, B. P.; Ghosh, L. K. (Drug Research, 2014)
Our objective is to synthesize the smaller chain N-linked and O-linked glycopeptides using sugars belong to mono, di and polysaccharides, with the efforts mainly directed towards the identification of antibacterial compounds. 7 glycopeptides, viz., Arg-Asn-Mannose, Arg-Asn-Lactose, His-Asn-Mannose, His-Asn-Lactose (N-glycopeptides), Arg-Ser-Lactose, Arg-Thr-Lactose, Arg-Thr-Starch (O-glycopeptides) were prepared by dicyclohexyl carbodimide (DCC) coupling for amino acids using microwave oven (50W power; 15 min) and activated and coupled with respective sugar moieties using microwave oven at 120 W for 20–25 min. The column eluted compounds were tested for disc diffusion assay using 3 gram positive S. aureus, B. subtilis, S. caprae and 3 gram negative E. coli, P. aeruginosa and S. sonnei strains at different concentrations predicted by pH and inhibitory concentrations. One of the test glycopeptide, His-Asn-Lactose was found to be very effective against all the microbial strains tested and 3 other Test Compounds, viz., His-Asn-Mannose, Arg-Thr-Lactose and Arg-Thr-Starch are also proved to be effective against 2 gram positive and 2 gram negative strains tested. Maximum activity was observed at a concentration of 450 μg/ml (747.51 µM) for the N-glycopeptide His-Asn-Lactose with the corresponding zonal inhibition diameters (15 mm; 19 mm; 14 mm; 18 mm; 16 mm; 17 mm) against S. aureus, B. subtilis, S. caprae, E. coli, P. aeruginosa, S. sonnei. This is the first evidence based report that our N-glycopeptide, His-Asn-Lactose tested, has shown antibacterial action against both gram positive and gram negative strains. Further in vivo testing and clinical studies will make sure to position our potent small chain N-glycopeptide in the arsenal of new broad spectrum anti-gram positive and negative agent.
Keywords: antibacterial drugs; drug research; infectious diseases